Comparison of health and environmental impacts from electricity generation systems. (1st January 2002) - Krewitt, Wolfram; Friedrich, Rainer; Trukenmuller, Alfred
Health and environmental impacts from fossil, renewable and nuclear electricity generation are estimated following a detailed bottom-up impact pathway analysis. By using a set of harmonised air quality and dose-effect models, a methodological framework has been established and consistently applied across different fuel chains, including the analysis of consequences from beyond design nuclear accidents. As far as possible, welfare losses resulting from environmental impacts are transferred into monetary terms to make results comparable on an aggregated level, and to indicate the costs to society resulting from health and environmental damage related to electricity generation.